The fluorescent probe-based recombinase-aided amplification for rapid detection of Escherichia coli O157:H7. (December 2021) - Mu, Dan; Zhou, Donggen; Xie, Guoyang; Liu, Ju; Xiong, Qin; Feng, Xiaoyan; Xu, Hengyi
Abstract: Escherichia coli O157:H7 ( E. coli O157:H7) is a common foodborne morbigenous microorganism, which can spread through fecal-oral transmission. Humans can be infected by ingesting foods and water contaminated with E. coli O157:H7, which can cause various symptoms. In present study, we have successfully developed a quick and hypersensitive fluorescent probe-based Recombinase-aided amplification (RAA) method and applied in E. coli O157:H7 detection at 39 °C in 20 min. The sensitivity of the assay in pure E. coli O157:H7 suspension was 5.6 × 10 0 CFU/mL. The fluorescent probe-based RAA assay was further applied in three samples, and the limit of detection (LOD) in skimmed milk, lettuces and lake water was 5.4 × 10 1 CFU/mL, 7.9 × 10 1 CFU/mL and 5.2 × 10 1 CFU/mL, separately. This method showed a high sensitivity and short detection time, which has the feasible application in on-site test in real samples. Highlights: RAA combined fluorescent probe achieved one step for amplification and read-out. RAA is rapid isothermal amplification and performed at 39 °C within 20 min. E. coli O157:H7 was detected by the proposed assay in multiple real samples.